The Difference of Enterprises Taxpayers Compliance after Tax Amnesty - Fitria, Dona; Abdillah, Agus; Prasetyono, Hendro; Cahyo, Ismail Dwi; Burhanudin, Burhanudin (Semarang State University, 2019)
The purpose of this study was to determine and analyze the compliance of enterprises taxpayers before and after the tax amnesty was applied in KPP Pratama South Jakarta. The research location was at KPP Pratama Jakarta Cilandak, KPP Pratama Jakarta Pancoran, KPP Pratama Jakarta Mampang, and KPP Pratama Jakarta Pasar Minggu. Data collection with documentation techniques, namely secondary data collection. Taxpayer’s compliance data for 2015, which is SPT as of March 2016, is assumed to be data before tax amnesty. While the 2016 taxpayer’s compliance data which is SPT as of March 2017 is assumed to be the data of the tax amnesty validity period. The data analysis technique in this study uses the SPT taxpayer compliance ratio 2016 - 2017. Statistical tests using Paried Sample t-Test. The results of the study showed that the amount of enterprises taxpayer compliance submitting timely Annual Tax Returns increased by 10.60% from 13.40% to 24.00%. Furthermore, the taxpayer’s compliance ratio that did not submit the Annual Tax Return decreased by 3.90%, namely in 2016 amounted to 76.92% to 73.02% in 2017. The Paired Sample t-Test has different Enterprises Taxpayer’s compliance before and after the enactment of tax amnesty.